PROLIFERATION AND ULTRASTRUCTURE OF PERIVASCULAR CELLS IN BONE TISSUE REMODELING ZONES AT REMOVAL SUPPORT LOADING - Rodionova N. V.; Skripchenko O. V.; Katkova O. V. (World of Medicine and Biology, 2015)
Using histological methods, electron microscopy and histoautography with 3H-thymidine was found that at long term hind limbs unloading the poorly differentiated perivascular cells of sinusoids are the main DNA- synthesizing fraction in the zones of adaptive transformations (metaphysis, cortical bone vascular channels in diaphysis) in rat femur. High proliferative activity of the population is connected not only to self-maintenance but also takes part in genesis of osteogenic cells. It was found, that under supportive unloading there is reduction of perivascular cells proliferation intensity in destruction zones, particularly in differentiating cells population, which includes preosteoblasts in remodeling zones. Part of the cells differentiates into fibroblasts, resulting in bone fibrosis zones emerge. Thus, there isn’t an adequate response of the bone tissues in destruction locus. The osteoporotic cavities are forming in bone tissue; mechanical density of bone structures is reducing.